"Interacting with the river of violence" Violence in a maximum-security correctional centre in South Africa - Kuyler, D; Van den Berg, JA (Nederduitse Gereformeerde Teologiese Tydskrif, 2008)
Perspectives portrayed in this article are the outcome of a participatory action researched process embodying principles underlying narrative therapy. The co-researchers and researchers embarked on conversations to find out whether religion does play a role in rehabilitation as described by the White Paper on Corrections. The heading of this paper is borrowed from a metaphor that arose from one of the discussions about violence in a prison situation. Expert knowledge on violence, the effects of witnessing violence, and the experience of the consequences of violence are portrayed. The research emphasizes the fact that Inmates converted to Christianity have acquired a new identity on different levels and, although being in prison, they are living from an alternative knowledge with meaning for everyday life. It is clear that religion can play a very positive role in changing perceptions and behaviour about violence amongst Inmates. A narrative, contextual, practical theology needs to take note of these perspectives in order to accommodate marginalized people within society. Once more I froze at the somehow surreal thought that I could be speaking in coded language with this man, that he could take me into his world of secrets and private language, and that I was becoming a part of that world… (Gobodo Madikizela 2003:35-36).